DEVELOPMENT OF TEACHER EDUCATION IN POLAND: THEORETICAL ASPECTS - Hryshchuk, Yuliya V. (Educological discourse, 2015)
In the article analyzes the problem of teacher education in the Republic of Poland in pedagogical theory. Important aspects of education degree in Poland considered the following areas: the development of music and teacher education; development of higher educational schools; development of higher education in private ownership; development of postgraduate teacher education; development of university education and research; educational reform; professional and pedagogical training of future professionals; the formation of different types of professional competence of future professionals.